Electronic canva module on quadratic function for junior hisch school student - Priwantoro, Soffi Widyanesti; Syariful Fahmi; RasyidaFaiz (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
Purpose: This study aims to develop a Canva-based interactive electronic module (e-module) to mitigate negative stigmas toward mathematics and address the scarcity of digital learning resources for quadratic functions at the secondary level. Design/methodology/approach: A Research and Development (R&D) design was employed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects included 20 students from class IX-E at SMP Muhammadiyah 9 Yogyakarta. Data were gathered through material and media expert validation instruments alongside student response questionnaires. Findings: Validation results yielded mean scores of 4.5 (Excellent) from material experts and 4.625 (Excellent) from media experts. Small and large-scale trials produced a student response mean score of 3.78 (Good), confirming the e-module’s feasibility and practicality for classroom implementation. Practical implications: Educators can utilize this e-module as an interactive self-study tool to enhance student engagement and simplify abstract quadratic function concepts. Originality/value: This study contributes to digital pedagogy literature by integrating Canva’s design capabilities into the formal mathematics curriculum to improve instructional appeal. Purpose: Penelitian ini bertujuan mengembangkan modul elektronik (e-modul) interaktif berbasis Canva untuk mengatasi stigma negatif terhadap matematika dan keterbatasan bahan ajar digital pada materi fungsi kuadrat di tingkat menengah. Design/methodology/approach: Menggunakan metode Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Subjek penelitian terdiri dari 20 siswa kelas IX-E SMP Muhammadiyah 9 Yogyakarta. Data dikumpulkan melalui instrumen validasi ahli materi, ahli media, dan angket respons siswa. Findings: Hasil validasi menunjukkan skor rata-rata 4,5 (Sangat Baik) dari ahli materi dan 4,625 (Sangat Baik) dari ahli media. Uji coba pada kelompok kecil dan besar menghasilkan skor rata-rata respons siswa sebesar 3,78 (Baik), membuktikan bahwa e-modul ini layak dan praktis digunakan. Practical implications: Guru dapat memanfaatkan e-modul ini sebagai media pembelajaran mandiri yang interaktif untuk meningkatkan keterlibatan siswa dan menyederhanakan konsep fungsi kuadrat yang abstrak. Originality/value: Studi ini memberikan kontribusi pada literatur media pembelajaran digital dengan mengintegrasikan fitur desain Canva ke dalam kurikulum matematika formal untuk meningkatkan daya tarik instruksional.